(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
Time is a relative phenomenon between two regions of space with different values of gravity because the rate of passage of time depends on the strength of the gravity field. In high gravity fields time slows down compared to low gravity fields where time speeds up. This implies that if one goes from living in a high gravity region to a low gravity region then one sees the future. On the other hand, going from a low gravity region to a high gravity region one sees the past. Gravity has the same effect on the human spirit as it has on the human body and on non-living things, all of which depend on the rate of passage of time. On earth the spirit in the human body is affected by the earth’s stronger gravity while a spirit without a body residing in the vacuum space of the quantum region where gravity has a negligible effect that depends only on the gravity due to the spirit’s mass-energy. Hence spirits in the human body on earth will age slower than spirits in the quantum world. Based on the calculated spirit’s mass-energy we prove that the spirit is quantum mechanical in nature.